2000
DOI: 10.1080/00207230008711309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen/phosphorus ratios on the productivity of Nile river phytoplankton

Abstract: Mixtures of different concentrations of both nitrogen and phosphorus were used at various N/P ratios to investigate the maximum growth of Nile River Phytoplankton using bioassay studies. A ratio 4:1 N/P gave a high algal mass production and high content of chl(a) of phytoplankton. A high diversity value 1.48 was obtained during the experimental run. Bacillanophyta was the dominant group followed by chlorophyta and cyanophyta in all treatments. The growth rate reached its maximum value (1.69) after 16 days of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The River Nile's water is already high in nutrients (both nitrogen and phosphorus) resulting in high productivity of phytoplanktons in the river [2]. A comparison of the heavy metal content of the River Nile's water in Cairo before and after treatment at four drinking water treatment plants showed that the treatment removed only 33% of lead and 53% of cadmium [3].…”
Section: Introductionmentioning
confidence: 98%
“…The River Nile's water is already high in nutrients (both nitrogen and phosphorus) resulting in high productivity of phytoplanktons in the river [2]. A comparison of the heavy metal content of the River Nile's water in Cairo before and after treatment at four drinking water treatment plants showed that the treatment removed only 33% of lead and 53% of cadmium [3].…”
Section: Introductionmentioning
confidence: 98%